Seven-Membered Lactam Derivatives of Podophyllotoxins as New Pesticidal Agents - Xiaoyan Zhi (Nature Portfolio, 2017)
Abstract As a continuation of our efforts to discover and develop natural-product-based insecticidal agents, three novel and unusual 7-membered lactam derivatives of podophyllotoxin were prepared by thionyl chloride-mediated ring-expanded Beckmann rearrangement. The steric configurations of 3a–c were unambiguously identified by X-ray crystallography. It demonstrated that the configuration of the picropodophyllotoxin C4-oximes could also be confirmed by the corresponding C-ring expansion products via Beckmann rearrangement. Moreover, it was obviously further testified that when picropodophyllones reacted with hydroxylamine hydrochloride, only E configuration of picropodophyllotoxin C4-oximes was selectively produced. Compounds 3b and 3c showed more potent pesticidal activity than toosendanin against oriental armyworm, Mythimna separata (Walker).